A study on stress-strain behaviour of granite and sandstone using closed circuit servo-controlled testing machine [compact disc] - 429033 Yung, Yi Chang (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2006